Enhancing Adolescent’s Emotion Regulation with Dialectical Behavior Therapy’s Skill Training: The Applications across Borderline, Mild, and Moderate Intellectual Disability - Safitri, Shahnaz (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Intellectual disability (ID) is characterized by significant limitations in intellectual and adaptive functioning emerging before the age of eighteen-years-old. Known as a pervasive developmental disorder, the disability disturbs the individual’s functioning on a wide range of cognitive and social realms, which further result in failure at school and interpersonal relationships. Nonetheless, the capacity for emotion regulation (ER) serves as a key role in supporting the individual’s adaptation despite having a disability. Researches have found that ER can be taught as a skill for those with ID, specifically using Dialectical Behavior Therapy’s (DBT) skill training as the basis for the program. Therefore, this study aims to examine further the application of this DBT program and its effectiveness in enhancing ER skills. The programs were delivered to three participants of adolescent aged (9-17 years old) in Indonesia, each having a moderate ID, mild ID, and borderline intellectual functioning (BIF). Using a single case study design (A-B-A procedure) where participants’ ER skills were measured before and after the program, these studies showed the program was effective. However, in terms of application, it is noteworthy to highlight the adjustments needed during the program’s delivery, considering the degree of disability. These adjustments are found in the program sequences, modality used for the program, the evaluation method used to record the participants’ improvements, and the degree of skills developed. This paper examines these variations in depth to shed light on the applicability of DBT’s program as in improving ER for individuals with ID and BIF.